Predictors of adverse events and early mortality after esophageal stent placement in a low resource setting: a series of 3823 patients in Kenya - Mwachiro, Michael; Parker, Robert; Lando, Justus; Simel, Ian; Chol, Nyail; Ranketi, Sinkeet; Chepkwony, Robert; Pyego, Linus; Chepkirui, Caren; Chepkemoi, Winnie; Fleischer, David; Dawsey, Sanford; Topazian, Mark; Burgert, Steve; White, Russell (Endoscopy International Open, 2022)
Background and study aims Dysphagia from esophageal cancer may be palliated with self-expanding metallic stents (SEMS). Controversy exists about the use of dilation before SEMS deployment.Patients and methods We performed a retrospective cohort study of patients who had SEMS placement without fluoroscopy for palliation at Tenwek Hospital in Bomet, Kenya between January 1999 and April 2019. The primary outcome was any serious adverse event (AE) (chest pain, stent migration, perforation, bleeding, or all-cause mortality) within 30 days of the procedure. Various demographic and clinical characteristics, and procedural details, were examined as risk factors. Technical success, defined as correct SEMS placement, and clinical success, defined as dysphagia score improvement without 30-day mortality, were examined.Results A total of 3823 patients underwent SEMS placement, with 2844 (74.4 %) placed in the second decade of the study. Technical and clinical success were achieved in 97.2 % and 95.5 %, respectively, with mean dysphagia scores improving from 3.4 (SD 0.6) to 0.9 (SD 1.3) post-stent placement. AEs occurred in 169 patients (4.4 %). AEs, specifically perforations, were associated with dilation to greater than 36F in the first decade. Perforation rates decreased from the first (4.1 %) to the second decade (0.2 %). Only 30% had complete 30-day follow-up data.Conclusions SEMS placement is a safe, effective method of palliating malignant dysphagia, with low rates of AEs and 30-day mortality and high rates of clinical and technical success. Dilation can facilitate placement of SEMS without fluoroscopy but should not be performed above 36F due to the risk of perforation.